Analysis of the expression of emotion in the oral narratives of Jordanian Arabic learners of Spanish. - Blanco Ruiz, Mónica; Pérez Serrano, Mercedes (Círculo de Lingüística Aplicada a la Comunicación, 2021)
The aim of this article is to analyze the expression of emotion in oral autobiographical narratives in Spanish as a foreign language of 20 Arabic speakers. Three film fragments inducing joy, sadness and one neutral were used. The informants filled a questionnaire where they ensured to have felt these emotions and they narrated events where they had experienced joy and sadness. We analyze the lexicon, focusing on complexity -density, diversity, and sophistication-, emotional vocabulary and the grammatical categories used to express emotion. There were no significant differences in lexical complexity, there were more positive than negative words - especially verbs, followed by nouns, adjectives, and adverbs - in both speeches, more negative words in the sadness speech than negative words in the joy speech and more sophisticated words. These results reveal the importance of emotional vocabulary in teaching in order to improve the socialization and acculturation of language knowing the different emotional scripts between cultures and languages
Keywords: emotional vocabulary; density; diversity; sophistication